A review of unconformity-type uranium deposits - Dabrowski, F A (Rhodes University, Faculty of Science, Department of Geology, 1980)
Intense interest in uranium in the past decade has led to the discovery of new kinds of deposits of which the so-called unconformity-type are economically the most important. Presently known occurrences are restricted to Australia and Canada where they are characterized chiefly by their spatial relationship to Lower-Middle Proterozoic unconformities. Other common features include similar host-rock assemblages, structural controls, alteration, mineralogy, age relationships and fluid-inclusion data. Similar characteristics in other vein-type deposits, including those of the Beaverlodge district in Canada, deposits in France and Portugal, and the Schwartzwalder mine in the United States, suggest that they may also be of the unconformity-type. Various interpretations of the geological relationships of unconformity-type deposits have resulted in a number of genetic hypotheses, which require different exploration philosophies. Nearsurface supergene processes are considered to be most important although other mechanisms may have played contributing roles in the concentration of uranium. There is considerable potential for further discoveries of unconformity-type uranium deposits throughout the world. No such deposits are yet known in southern Africa although several favourable Precambrian unconformities are present.
Keywords: Uranium ores; Mineralogy; Geochemistry; Unconformities (Geology)